2016
DOI: 10.1002/mus.24741
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and cardiac function in japanese patients with dysferlinopathy

Abstract: Patients with dysferlinopathy may develop severe respiratory failure and latent cardiac dysfunction. Both respiratory and cardiac function should be monitored diligently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 20 publications
2
36
1
Order By: Relevance
“…This is the first report of a patient with ANO5 ‐related muscular dystrophy who started with non‐invasive ventilation. Cardiac dysfunction and respiratory insufficiency are known to be a frequent complication of the sarcoglycanopathies and LGMDR9/LGMD2I but has only recently been described in LGMDR1/LGMD2A and the dysferlinopathies . There are conflicting reports on cardiac dysfunction in ANO5 ‐related muscular dystrophy .…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of a patient with ANO5 ‐related muscular dystrophy who started with non‐invasive ventilation. Cardiac dysfunction and respiratory insufficiency are known to be a frequent complication of the sarcoglycanopathies and LGMDR9/LGMD2I but has only recently been described in LGMDR1/LGMD2A and the dysferlinopathies . There are conflicting reports on cardiac dysfunction in ANO5 ‐related muscular dystrophy .…”
Section: Discussionmentioning
confidence: 99%
“…32 Four patients used nocturnal ventilation and reported sleep apnea. This may be coincidental as all have FVC ≥50% and 3 patients have body mass index >30.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac abnormalities have previously been reported in dysferlinopathy, but whether these are a consequence of dysferlinopathy or an alternative etiology is not established. 9,3235 Low serum creatinine seen in 70% of patients is relevant for renal function monitoring, as creatinine-dependent methods will be uninformative. 36 …”
Section: Discussionmentioning
confidence: 99%
“…A cardiac MRI study showed subclinical myocardial fibrosis in 33% of patients, which was associated in half of cases with diastolic dysfunction . Many patients develop latent cardiac dysfunction, and a few patients have dilated cardiomyopathy, other cardiac rhythm changes, or left ventricular hypertrophy . One patient died with hypertrophic obstructive cardiomyopathy and supra‐ventricular tachycardia requiring pacing …”
Section: Clinical Featuresmentioning
confidence: 99%
“…In a 23‐year follow‐up study to investigate disease progression, many patients developed restrictive lung disease with mild obstructive signs in small airways, reduced forced vital capacity, and severe respiratory failure . In another series, some patients needed noninvasive ventilation, and 1 died of respiratory failure …”
Section: Clinical Featuresmentioning
confidence: 99%